Social Networks and Surviving the Holocaust - Matěj Bělín; Tomáš Jelínek; Štepán Jurajda (Institute of Labor Economics (IZA), 2022)
Survivor testimonies link survival in deadly POW camps, Gulags, and Nazi concentration camps to the formation of close friendships with other prisoners. We provide statistical evidence consistent with these fundamentally selective testimonies. We study the survival of the 140 thousand Jews who entered the Theresienstadt ghetto, where 33 thousand died and from where over 80 thousand were sent to extermination camps. We ask whether an individual's social status prior to deportation, and the availability of potential friends among fellow prisoners influenced the risk of death in Theresienstadt, the ability to avoid transports to the camps, and the chances of surviving Auschwitz. Pre-deportation social status protected prisoners in the self-administered society of the Theresienstadt ghetto, but it was no longer helpful in the extreme conditions of the Auschwitz-Birkenau concentration camp. Relying on multiple proxies of pre-existing social networks, we uncover a significant survival advantage to entering Auschwitz with a group of potential friends.
Keywords: Z1; 330; social status; social networks; Holocaust Survival; Nazi concentration camp; ghetto; Theresienstadt/Terezín; Auschwitz-Birkenau